Against Orthodoxy - Aronowitz, S. author. aut Link
VIII, 189 p.
Keywords: The book contains groundbreaking and immersive essays on crucial 20th Century scholars on social theory, discussed and analyzed from a radical, critical theory perspective. Aronowitz provides his unique and lauded critical eye toward the leading thinkers of our age, crafting an immersive set of essays on radical thought.